Интернет-технологии в обучении студентов-заочников биомедицинской электронике - Прасол, И. В.; Прасол, Р. И. (УАДО, 2002)
The questions of study by the students of correspondence branch of disciplines on biomedical electronics with use the Internet technologies are considered. The structure of a training site ensuring interactive mastering of a material is offered. The sections are stipulated: an educational material, testing, practical tasks, forum, guest book, feedback etc
Keywords: биомедицинская электроника; обучение студентов-заочников